2021
DOI: 10.1093/ndt/gfab055
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of vadadustat compared with darbepoetin alfa in Japanese anemic patients on hemodialysis: a Phase 3, multicenter, randomized, double-blind study

Abstract: Background Vadadustat is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor that stimulates erythropoiesis. Methods The efficacy and safety of vadadustat, compared with darbepoetin alfa, was determined in a phase 3 double-blind study in Japanese anemic patients on hemodialysis. Patients receiving erythropoiesis-stimulating agents (ESAs) were randomized and switched to either vadadustat or darbepoetin alfa for 52 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 23 publications
3
73
0
Order By: Relevance
“…13,14 In the present study, the high incidences of TEAEs observed in both treatment groups were not surprising in this patient population and were in line with published data. 16,18 There were numeric imbalances in the incidences of TEAEs resulting in discontinuation (including neoplasms considered by the investigator to be unrelated to study drug), of ocular AEs, of moderate and severe TEAEs, and in the number of patients who received rescue treatment that favored darbepoetin. Interestingly, in patients not receiving dialysis, the incidences of neoplasms and ocular AEs were similar between molidustat (3.7% and 19.5%, respectively) and darbepoetin (4.9% and 20.7%, respectively).…”
Section: Iron Treatmentmentioning
confidence: 99%
“…13,14 In the present study, the high incidences of TEAEs observed in both treatment groups were not surprising in this patient population and were in line with published data. 16,18 There were numeric imbalances in the incidences of TEAEs resulting in discontinuation (including neoplasms considered by the investigator to be unrelated to study drug), of ocular AEs, of moderate and severe TEAEs, and in the number of patients who received rescue treatment that favored darbepoetin. Interestingly, in patients not receiving dialysis, the incidences of neoplasms and ocular AEs were similar between molidustat (3.7% and 19.5%, respectively) and darbepoetin (4.9% and 20.7%, respectively).…”
Section: Iron Treatmentmentioning
confidence: 99%
“…Vadadustat A 52-week phase 3 study of vadadustat vs. darbepoetin among 323 DD-CKD patients in Japan revealed efficacy noninferiority for vadadustat and no safety concerns. 58 In an open-label phase 3 24-week study of 42 Japanese PD patients vadadustat was well-tolerated and maintained target Hb levels. 59 The global phase 3 program for vadadustat includes INNO 2 VATE for DD-CKD patients 60 and PRO 2 TECT for NDD-CKD patients.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 97%
“…Collectively, data from clinical trials of HIF-PH inhibitors, namely roxadustat [115][116][117][118][119][120][121][122][123][124][125][126][127], daprodustat [128][129][130][131][132][133][134][135], desidustat [136], enarodustat [137,138], molidustat [139][140][141][142][143], and vadadustat [144][145][146][147][148][149], have clearly shown these agents are efficacious in increasing Hb and decreasing hepcidin levels in patients with anemia of CKD (Table 2). Indeed, a recent meta-analysis of 22 trials found that HIF-PH inhibitors provided a 0.96 and 1.78 g/dL greater weighted mean increases of Hb levels from baseline compared with control (placebo or ESA) in patients with DD-CKD or NDD-CKD, respectively [150].…”
Section: Hif-ph Inhibitorsmentioning
confidence: 99%